Gut microbiota from Mori fructus (Morus alba L.) polyphenols and polysaccharides-dosed mice activates the PPARα/PGC-1α signaling pathway to mitigate HFD-induced metabolic syndrome in mice - Meixia Wan; Qing Li; Yudie Xiao; Dan Zhou; Qianya Lei; Shu Wang (Scientific Reports)
Abstract Mori Fructus, rich in polysaccharides and polyphenols, has long been used in East Asia as a functional food and medicinal agent. In traditional Chinese medicine, it is used to treat various ailments like wasting-thirst syndrome and constipation. Studies suggest its extract fractions may alleviate metabolic syndrome symptoms by affecting gut microbiota. To explore this, fecal microbiota transplantation (FMT) was used in an experiment. Pseudo-germ-free mice were created with antibiotics and given a high-fat, high-sugar diet (HFD) to induce metabolic syndrome. Then, fecal bacterial infusions were transplanted. Results showed significant improvement in metabolic syndrome parameters in the FMT-MFPS(fecal microbiota transplantation-Mori Fructus polyphenols plus polysaccharides) group. Dyslipidemia, liver, and kidney injuries were modulated in treated mice. The PPARα/PGC-1α signaling pathway was activated. These findings indicate Mori Fructus extract fractions prevent metabolic syndrome via gut microbiota modulation, with effects sustained through FMT, providing a reference for prevention.